Direct detection of infectious bursal disease virus from clinical samples by in situ reverse transcriptase-linked polymerase chain reaction - Cardoso, Tereza C. [UNESP]; Rosa, Ana C. G.; Astolphi, Rafael D. [UNESP]; Vincente, Rafael M. [UNESP]; Novais, Juliana B. [UNESP]; Hirata, Karina Y. [UNESP]; Luvizotto, Maria Cecilia R. [UNESP] (Taylor & Francis Ltd, 2008)
The presence of the very virulent (vv) Brazilian strain of infectious bursal disease virus (IBDV) was determined in the bursa of Fabricius, thymus and liver of 2-week-old broilers from a flock with a higher than expected mortality. For this purpose, a direct in situ reverse transcriptase (RT)-linked polymerase chain reaction (PCR) method was developed using specific primers for vvIBDV. Unlabelled forward and reverse biotinylated oligonucleotides were used for RT-PCR in a one-step method and the respective products were revealed by a direct enzymatic reaction. The results were compared with those obtained by standard RT-PCR using general primers for IBDV and virus isolation. The virus isolation, RT-PCR and in situ RT-PCR revealed positive results on the bursa of Fabricius in 86%, 80% and 100%, respectively. The in situ RT-PCR detected vvIBDV in all tested thymus and liver samples, whereas the standard RT-PCR detected virus in 80% and 90% of the samples, respectively. After three consecutive passages on chicken embryonated eggs, IBDV was isolated from 64% of the thymus samples and 30% of the liver samples. In the present study, no classical or antigenic variants of IBDV were detected. The developed in situ RT-PCR assay was able to detect the very virulent strain of IBDV with a higher sensitivity than the conventional RT-PCR and virus isolation.